2015
DOI: 10.1038/onc.2015.334
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PYK2 mediates microenvironment-specific cell death in multiple myeloma

Abstract: Multiple myeloma (MM) remains an incurable malignancy due, in part, to the influence of the bone marrow microenvironment on survival and drug response. Identification of microenvironment-specific survival signaling determinants is critical for the rational design of therapy and elimination of MM. Previously, we have shown that collaborative signaling between β1 integrin-mediated adhesion to fibronectin and interleukin-6 confers a more malignant phenotype via amplification of signal transducer and activator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…The progression of MM involves primary cytogenetic abnormalities (cyclin D, fibroblast growth factor receptor 3, histone-lysine N-methyltransferase, or musculoaponeurotic fibrosarcoma) in myeloma-initiating cells. The oncogenic growth of MM cells is hypothesized to be supported by intracellular oncogenic events and tumor microenvironment components, such as bone marrow stromal cells (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The progression of MM involves primary cytogenetic abnormalities (cyclin D, fibroblast growth factor receptor 3, histone-lysine N-methyltransferase, or musculoaponeurotic fibrosarcoma) in myeloma-initiating cells. The oncogenic growth of MM cells is hypothesized to be supported by intracellular oncogenic events and tumor microenvironment components, such as bone marrow stromal cells (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Jakubowiak and his group, using Carfilzomib in combination with lenalidomide and low-dose dexamethasone, in MM, achieved sCR rate of 42%, a result never before reached (Jakubowiak et al, 2012). It has been shown that disease progression or relapse are primarily due to residual myeloma reservoirs through environmentmediated drug resistance and/or the persistence of myeloma stem cells Allegra, Alonci, Penna, et al, 2014;Meads et al, 2016;Shain & Dalton, 2009;.…”
Section: Response Changes Between Old and New Drugsmentioning
confidence: 99%
“…Recent studies indicate that interaction between β1 integrin, fibronectin, and interleukin‐6 in bone marrow microenvironment results in increased activation of Pyk2, resulting in amplification of signal transducer and activator of transcription 3 (STAT3) activation. Molecular and pharmacological targeting of Pyk2 results in attenuated MM progression in vivo [Meads et al, ]. Interestingly, the dependency of Pyk2 in mediating survival in these studies was more notable when MM cells were placed in co‐culture with bone marrow stroma cells compared to unicellular MM model.…”
Section: Agents That Target the Bone Marrow Microenvironmentmentioning
confidence: 99%